Cervical tubercular lymphadenitis accompanying with pulmonary tuberculosis – a case report - Makuch, Marcelina; Makuch, Marcin; Terlecka, Paulina; Michnar, Marek; Milanowski, Janusz (Journal of Education, Health and Sport, 2019)
Tuberculosis (TB) is still one of the major public health problems worldwide. TB is an infectious disease caused by Mycobacterium tuberculosis. It typically affects the lungs (pulmonary tuberculosis), but may also occur in other sites (extrapulmonary tuberculosis). Cervical tubercular lymphadenitis is one of the most common localizations of extrapulmonary tuberculosis [1,2]. We present a case of a 57-year old man with a history of 3-month weakness and swollen, bilaterally inflamed cervical lymph nodes. Cervical tubercular lymphadenitis accompanying with pulmonary tuberculosis was diagnosed. Moreover, we carry out the differential diagnosis of the cervical lymphadenopathy.